Does Low‐Level Substitution Aid in Improving Thermoelectric Properties? A Case Study of M0.1Ni0.9Cr2S4 (M = Mn, In). Issue 3 (28th October 2021) - Groß, Hendrik; Poschmann, Michael; Groeneveld, Dennis; Koenig, Jan D.; Kienle, Lorenz; Bensch, Wolfgang
Abstract : The influence of low‐level metal cation substitution in the thermoelectric material NiCr2 S4, treated via field‐assisted sintering, is investigated in X‐ray diffraction (XRD) and transmission electron microscopy (TEM) studies. NiCr2 S4 and Mn0.1 Ni0.9 Cr2 S4 can be synthesized and compacted as phase‐pure pellets, while In0.1 Ni0.9 Cr2 S4 appears as a mixture of different phases. XRD investigations reveal that Mn can be incorporated into the host material's Ni lattice sites, while In is mainly incorporated into additional phases. Both NiCr2 S4 and Mn0.1 Ni0.9 Cr2 S4 form a structure of chemically segregated, nanoscale domains, which appear significantly more pronounced for Mn0.1 Ni0.9 Cr2 S4 . All materials exhibit similar, promising thermal conductivities around 2.0 W m −1 K −1, with Seebeck coefficients ranging from −55 to −65 μV K −1 . Only the electrical conductivity is noticeably influenced by the substitutions, with the highest value of 504 S cm −1 obtained for the pristine material, and subsequently declining for both substituted phases. Abstract : Pristine NiCr2 S4 and cation substitutions M0.1 Ni0.9 Cr2 S4 (M = Mn, In) are synthesized and compacted via field‐assisted sintering technique (FAST). NiCr2 S4 and Mn0.1 Ni0.9 Cr2 S4 are obtained as phase‐pure pellets and exhibit the formation of nanoscale domains. In0.1 Ni0.9 Cr2 S4 remains homogeneous and forms additional phases. Cation substitution mainly affects the electrical conductivity, which is lowered by the addition of Mn or In.